The Mediating Role of the Achievement Emotions in the Relationship between Class Psychosocial Climate and Academic Burnout - somayyeh hashemi; zahra hashemi; zahra naghsh (پژوهش در نظام‌های آموزشی, 2018)
The aim of this study was to investigate the mediatory role of the achievement emotions in relationship with class psychosocial climate, and academic burnout to illustrate the relationship between research variables in the causal model. The research population consisted of all students of Alzahra University in Tehran, among them 300 students were selected through random multi-stage cluster sampling. The instruments for data gathering were: a short version of the achievement Emotions Questionnaire (PEGQ), Goetz & Perry (2005), the Questionnaire of Joe Psychosocial class of Fraser, Giddings and McBurray (1995), and the Academic Burnout Questionnaire (Salmela Arrow et al., 2009). The validity of the questionnaires were confirmed by statistical factor analysis. To examine reliability of the measures, Cronbach alpha coefficient was used. Two hypothetical models were tested by path analysis. The indicators of the results showed that the goodness of fit statistics are very suitable in both models. This means that both models are well supported by the empirical data and the mediatory role of positive and negative of the achievement emotions in the relationship between exogenous and endogenous variables was verified. The findings of the path analysis showed that the direct effects of adaptive and non-adaptive the class psychosocial climate (solidarity and friction), on the positive emotions (positive and negative), and the direct effect of the positive and negative progressive emotions on the academic burnout were significant. The non-direct effects of adaptive and non-adaptive the class psychosocial climate (solidarity and corruption), on the academic burnout were significant. In the mediating model, positive emotional was 39% of academic burnout and 36% for positive emotional variance and negative emotion was mediated by 42% of variance of academic burnout and 38% of negative emotion variance. Implications and suggestion for future studies are discussed.